FEBRILE INFECTION-RELATED EPILEPSY SYNDROME (FIRES) IN SCHOOLCHILDREN: LITERATURE REVIEW AND OWN OBSERVATIONS - S. L. Kulikova; S. A. Likhachev; S. A. Belaya; T. V. Svinkovskaya; A. R. Kashyna (Русский журнал детской неврологии, 2017)
FIRES (febrile infection-related epilepsy syndrome) – an epileptic syndrome that presents with multifocal refractory status epilepticus in previously normal children following a nonspecific febrile illness and evolves into a chronic, refractory, focal epilepsy with associated cognitive and behavioral difficulties. The article provides an overview of the literature on the etiology, diagnosis, clinical manifestations and treatment of this disease. We describe our own experience of observing the 4 patients with FIRES with the onset at the age from 4 to 14 years, with status epilepticus of duration from 3 to 27 days. All patients required intensive care treatment using burst-suppression coma and ventilatory support. Analysis of the cerebrospinal fluid, magnetic resonance imaging were no significant during the acute period in all patients. In one case, herpes simplex virus 6 type was detected by polymerase chain reaction in the serum and leucocytes. All patients were treated with antiepileptical, antiviral and antimicrobial drugs, steroids and IVIG. After status epilepticus drug-resistant epilepsy developed in all children. Two patients had mild cognitive impairment, the other 2 – severe. Light motor disturbances occurred in 2 children, 1 child had severe spastic tetraparesis. Interictal electroencephalography in chronic phase in 3 of 4 patients identified diffuse slowing of cortical rhythm, in 2 cases – epileptiform activity in the form of a spike-and-wave, sharp–slow wave in the fronto-temporal areas, in 1 case – the continuation irregular slow in the frontotemporal region. Follow-up magnetic resonance imaging was performed in 3 cases: 2 were normal and 1 had mild diffuse cortical atrophy.FIRES resulted in the development of drug-resistant epilepsy and cognitive impairment in all cases.